Plotting of Ethylene Glycol Blood Concentrations Using Linear Regression before and during Hemodialysis in a Case of Intoxication and Pharmacokinetic Review - Youngho Kim (Case Reports in Nephrology)
Introduction. As blood concentration measurement of commonly abused alcohol is readily available, the equation was proposed in previous publication to predict the change of their concentration. The change of ethylene glycol (EG) concentrations was studied in a case of intoxication to estimate required time for hemodialysis (HD) using linear regression. Case Report. A 55-year-old female with past medical history of seizure disorder, bipolar disorder, and chronic pain was admitted due to severe agitation. The patient was noted to have metabolic acidosis with elevated anion gap and acute kidney injury, which prompted blood concentration measurement of commonly abused alcohol. Her initial EG concentration was 26.45 mmol/L. Fomepizole therapy was initiated, soon followed by HD to enhance clearance. Discussion. Plotting of natural logarithm of EG concentrations over time showed that EG elimination follows first-order kinetics and predicts the change of its concentration well. Pharmacokinetic review revealed minimal elimination of EG by alcohol dehydrogenase (ADH) which could be related to genetic predisposition for ADH activity and home medications as well as presence of propylene glycol. Pharmacokinetics of EG is relatively well studied with published parameters. Consideration and application of pharmacokinetics could assist in management of EG intoxication including HD planning.